Shaping international campuses in China: the interplay of policy, economy, and culture in higher education leadership - Xiaofei, Chen; Mustakim, Siti Salina; Hassan, Aminuddin (Human Resources Management Academic Research Society (HRMARS), 2024)
Internationalization has emerged as a key component of higher education, offering significant advantages to students, staff, and institutions all around the world. However, universities are under more pressure to prepare students for the global market. The success of an institution's internationalization programs is significantly influenced by university executives, particularly those navigating the complexities of a unique cultural and organizational landscape. This paper delves into the role of government policy, economic conditions and organizational culture in this context, aiming to provide insights into leadership styles that facilitate the internationalization of higher education. This paper contributes to a more comprehensive framework that can inform strategic decision-making and enhance the effectiveness of internationalization efforts in the unique educational landscape of Guizhou.